Maternal SARS-CoV-2 sero-surveillance using newborn dried blood spot (DBS) screening specimens highlights extent of low vaccine uptake in pregnant women. Issue 5 (30th November 2022) - Moat, Stuart J.; Hillier, Sharon; de Souza, Sikha; Perry, Malorie; Cottrell, Simon; Lench, Alex; Payne, Heather; Jolles, Stephen
ABSTRACT: SARS-CoV-2 vaccine uptake in pregnant women is believed to be low and lags behind the general population contributing to increased hospital admissions, and poor maternal and fetal outcomes. However, there is a paucity of information on the SARS-CoV-2 serostatus of pregnant women to help inform policy planning and assess impact of interventions to improve vaccine uptake in this at-risk group. We analyzed 8, 683 residual, anonymized newborn screening dried bloodspot (DBS) specimens during a 15-month period (October 2020 to December 2021) in Wales (UK) for SARS-CoV-2 IgG-antibodies. We compared newborn DBS antibody-positive rates to the percentage number of pregnant women vaccinated and the percentage number of antibody-positive adults. In December 2021, 47.8% of women in Wales had received two doses of the vaccine by their delivery date; however, only 41.1% of DBS specimens had high antibody concentrations. Results indicate that a proportion of pregnant women remain at higher-risk of COVID complications, particularly given the reduction in antibody neutralization of Omicron versus the Delta variant. Our study demonstrates the utility of newborn screening DBS specimens to monitor SARS-CoV-2 serostatus in pregnant women representing maternal vaccination and natural infection in almost real-time, defining the immunity gap and impact of any interventions.